1996
DOI: 10.1074/jbc.271.37.22514
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Gene Encoding the Acyl-CoA-binding Protein ( ) Perturbs Acyl-CoA Metabolism in

Abstract: The ACB1 gene encoding the acyl-CoA-binding protein (ACBP) was disrupted in Saccharomyces cerevisiae. The disruption did not affect the growth rate on glucose but reduced the growth rate on ethanol slightly. Although the growth rate of the acb1-disrupted cells was unaffected or only slightly affected, the acb1-disrupted strain was unable to compete with wild type cells when grown in mixed culture. The acyl-CoA level in the disrupted cells was increased from 1.5- to 2.5-fold during exponential growth. The incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 23 publications
(28 reference statements)
2
97
2
Order By: Relevance
“…acyl-CoA thioesters versus lipid-bound oxygen esters, this result is not surprising. Quantitative acyl-CoA measurements with yeast have shown that lipid-bound acyl groups exceed acyl-CoA thioesters by a factor of about 2000 (35). With the method used in the present study and in the presence of 500 M exogenous fatty acid, we found even larger factors (data not shown).…”
Section: Discussioncontrasting
confidence: 44%
“…acyl-CoA thioesters versus lipid-bound oxygen esters, this result is not surprising. Quantitative acyl-CoA measurements with yeast have shown that lipid-bound acyl groups exceed acyl-CoA thioesters by a factor of about 2000 (35). With the method used in the present study and in the presence of 500 M exogenous fatty acid, we found even larger factors (data not shown).…”
Section: Discussioncontrasting
confidence: 44%
“…41,176 An acyl-CoA binding protein, Acb1p, is thought to bind the acyl chain and hand it over to cellular processes that consume acyl-CoA. 220 173,253 The encoding gene, OLE1/MDM2, has been demonstrated to be also involved in partitioning of mitochondria between mother and daughter cells. The ole1/mdm2 mutants are viable when fed unsaturated fatty acids.…”
Section: A Brief Survey On the Biosynthesis Of Fatty Acids In Yeastmentioning
confidence: 99%
“…These proteins, initially discovered as an impurity in a FABP preparation (Mogensen et al 1987), constitute a family that is well conserved over all eukaryotic species (Knudsen et al 1999). In yeast, overexpression experiments have shown its role in acylCoA pool formation (Mandrup et al 1993;Knudsen et al 1994); and gene disruption strongly suggests a role in transport (Schjerling et al 1996).…”
Section: Cytoplasmic Fatementioning
confidence: 99%